2019
DOI: 10.1177/0300060519856154
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal stump closure with polymeric clips is a reliable alternative to endostaplers

Abstract: Objective: Polymeric (Hem-o-lok) clips represent a novel technique with which to ligate the appendiceal stump following laparoscopic appendectomy. We compared the outcomes of using polymeric clips versus endostaplers for complicated and uncomplicated appendicitis. Methods: Six hundred seventy-three consecutive patients undergoing laparoscopic appendectomy with polymeric clips or endostaplers for acute appendicitis were assessed. The primary outcome was the incidence of intra-abdominal abscesses. Predictors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Still, the cutting injury may lead to a damaging inflammation caused by the rupture of the muscle fibres in the appendix wall; in severe cases, the mucosa can be injured, and the intestinal flora transferred to cause abdominal infection. Studies have shown that the incidence of abdominal infection after laparoscopic appendectomy with a cutting closure device is high; if the appendix stump is double ligated with a ligator device and the distance between the two ligature lines is more than 2 mm, the incidence of postoperative abdominal infection may be increased [ 30 ]. No difference was reported in the incidence of intra-abdominal infection after appendiceal stump ligation with a [ 31 ] ligator (that is, simple silk ligation of the appendiceal stump) compared with a Hem-o-lok clamp alone.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the cutting injury may lead to a damaging inflammation caused by the rupture of the muscle fibres in the appendix wall; in severe cases, the mucosa can be injured, and the intestinal flora transferred to cause abdominal infection. Studies have shown that the incidence of abdominal infection after laparoscopic appendectomy with a cutting closure device is high; if the appendix stump is double ligated with a ligator device and the distance between the two ligature lines is more than 2 mm, the incidence of postoperative abdominal infection may be increased [ 30 ]. No difference was reported in the incidence of intra-abdominal infection after appendiceal stump ligation with a [ 31 ] ligator (that is, simple silk ligation of the appendiceal stump) compared with a Hem-o-lok clamp alone.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative variables can be categorized in either two (= binary, e.g., gender: male and female) or more categories (= nominal, where the variables nominate a condition, e.g., blood types). [8] Important to know: It is not allowed to calculate nominal variables; neither if numbers are assigned to nominal variables (e.g., male = 0, female = 1). Ordinal variables are a special subgroup of nominal variables where the groups can be arranged in a logic order.…”
Section: Qualitative Variablesmentioning
confidence: 99%
“…In cases of small sample sizes (in a 2 × 2 table, if one of the fields expected value is < 5; in larger tables, if > 20% of the fields have an expected value < 5), a Fishers exact test should be used [8]. The Fishers exact test is less powerful, but it does not require a minimal number of entries for each field.…”
Section: Qualitative Data Analysis: Crosstables and Chi-squared Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1991, Jacobs et al first described the feasibility of colectomy by video-assisted, endoscopic surgery, without laparotomy [70], which offered reduced postoperative morbidity, faster oral feeding, and shorter hospital stay [71]. Nowadays, laparoscopy is more prevalent and applied to both simple [72][73][74] and complex [75] surgical cases. Although technically more difficult, after a learning curve, laparoscopic resection has shown equivalent operative results to conventional open colectomy [76].…”
Section: Intraoperative Risk Factorsmentioning
confidence: 99%